Speelhoven 83. (Aarschot : Vincent Halflants, 1983)
Bruyninckx, Robert ; Coeckelberghs, Luc ; Dries, Jan ; Gees, Paul ; Halflants, Vincent ; Hubert, Pierre ; De Luyck, Philippe ; Lybeer, Leen ; Navez, Jean-Marc ; Oosterlynck, Baudouin ; Van Rafelghem, Paul ; Van Snick, Philippe ; Swennen, Walter ; Verschueren, Bob ; Villers, Bernard
Speelhoven 83., Aarschot, 11.09 - 02.10.1983
Frans
Nederlands
kunstcatalogus